Optimization of Proportional Integral Controller’s Gain for Speed Control in Direct Torque Control Strategy Using Genetic Algorithm - Dr. Nour Mohammed, Dr.Benali Abdelkrim, Dr.Tadjeddine Ali, Dr.Bendelhoum Mohammed Sofiane (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The use of PI controllers in electrical machine drives is often characterized by the high effect of motor parameters changing; themain purpose of the presented paper is to adaptboth proportional and integral gains in order to perform and improve a closed-loop speed-controlled induction motor using direct torque control. First, a mathematical model is built using electrical and mechanical equations, then the DTC control method for the induction machine is presented based on relationship blocs; all those blocs are sensitized by the Simulink toolbox environment in MATLAB Software. The speed control is optimized by an optimized PI controller using genetic algorithm; the comparative simulation results are presented in order to claim the improvement of the system.